1981
DOI: 10.1172/jci110363
|View full text |Cite
|
Sign up to set email alerts
|

Selective Effects of Glucocerebroside (Gaucher's Storage Material) on Macrophage Cultures

Abstract: A B S T R A C T Although the enzymatic lesion inGaucher's disease is well established, little is known concerning the pathogenic mechanisms involved in the clinical manifestations of the disease. In order to obtain insight into this unexplored aspect of Gaucher's disease, we examined the effects of glucocerebroside (GL1) at the cellular level in monolayers of cultured murine macrophages. The addition of GL1 to these cultures stimulated the macrophages to release increased amounts of lymphocyte-activating facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In addition, several cytokines, including TNF, have proven to induce activation of coagulation and fibrinolysis (van der Poll et al, 1990(van der Poll et al, , 1991. In vitro observations have suggested a role for IL1 in the pathophysiology of Gaucher disease (Gery et al, 1981). We did not find elevated TNF and IL6 levels in serum of type 1 Gaucher disease patients (unpublished data); however, increased local production can not be excluded.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, several cytokines, including TNF, have proven to induce activation of coagulation and fibrinolysis (van der Poll et al, 1990(van der Poll et al, , 1991. In vitro observations have suggested a role for IL1 in the pathophysiology of Gaucher disease (Gery et al, 1981). We did not find elevated TNF and IL6 levels in serum of type 1 Gaucher disease patients (unpublished data); however, increased local production can not be excluded.…”
Section: Discussionmentioning
confidence: 55%
“…In line with this hypothesis of activation of Gaucher cells is the observation that glucocerebroside stimulates lipopolysaccharide-stimulated interleukin-1 production by murine macrophages. 34 In our previous study we have shown that REE is increased in the GD patients by Ç30% compared with healthy controls. 3 This is confirmed by a larger series of patients in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…The correlation of M-CSF, sCD14 and IL8 levels with disease manifestations suggests this. Further support is found in the fact that in vitro activation with LPS of murine macrophages, pre-incubated with glucosylceramide, are capable of enhanced IL1 production (8). However, it should be stressed that sCD14 can also be released by monocytes and IL8 and M-CSF can be produced by many other cell-types.…”
Section: Discussionmentioning
confidence: 96%
“…A role for cytokines in the pathophysiology of the disease has been suggested previously (1,3,7). Indeed, in vitro stimulation of murine macrophages with glucosylceramide has revealed enhanced production of IL1 (8). Recently, elevated plasma levels of TNFa were reported in some patients with Gaucher disease (9).…”
Section: Introductionmentioning
confidence: 99%